Biliary-Atresia-Associated Mannosidase-1-Alpha-2 Gene Regulates Biliary and Ciliary Morphogenesis and Laterality - So, Juhoon; Ningappa, Mylarappa; Glessner, Joseph; Min, Jun; Ashokkumar, Chethan; Ranganathan, Sarangarajan; Higgs, Brandon W.; Li, Dong; Sun, Qing; Schmitt, Lori; Biery, Amy C.; Dobrowolski, Steven; et al. (Frontiers in Physiology, 2020)
Background/Aims: Infectious and genetic factors are invoked respectively in isolated biliary atresia (BA), or syndromic BA, with major extrahepatic anomalies. However, isolated BA is also associated with minor extrahepatic gut and cardiovascular anomalies and multiple susceptibility genes, suggesting common origins. Methods: We investigated novel susceptibility genes with genome-wide association, targeted sequencing and tissue staining in BA requiring liver transplantation, independent of BA subtype. Candidate gene effects on morphogenesis, developmental pathways, and ciliogenesis, which regulates left-right patterning were investigated with zebrafish knockdown and mouse knockout models, mouse airway cell cultures, and liver transcriptome analysis. Results: Single nucleotide polymorphisms in Mannosidase-1-α-2 (MAN1A2) were significantly associated with BA and with other polymorphisms known to affect MAN1A2 expression but were not differentially enriched in either BA subtype. In zebrafish embryos, man1a2 knockdown caused poor biliary network formation, ciliary dysgenesis in Kupffer’s vesicle, cardiac and liver heterotaxy, and dysregulated egfra and other developmental genes. Suboptimal man1a2 knockdown synergized with suboptimal EGFR signaling or suboptimal knockdown of the EGFR pathway gene, adenosine-ribosylation-factor-6, which had minimal effects individually, to reproduce biliary defects but not heterotaxy. In cultured mouse airway epithelium, Man1a2 knockdown arrested ciliary development and motility. Man1a2-/- mice, which experience respiratory failure, also demonstrated portal and bile ductular inflammation. Human BA liver and Man1a2-/- liver exhibited reduced Man1a2 expression and dysregulated ciliary genes, known to cause multisystem human laterality defects. Conclusions: BA requiring transplantation associates with sequence variants in MAN1A2. man1a2 regulates laterality, in addition to hepatobiliary morphogenesis, by regulating ciliogenesis in zebrafish and mice, providing a novel developmental basis for multisystem defects in BA.